2016
DOI: 10.1182/blood-2016-02-698092
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing of refractory myeloma reveals a high incidence of mutations in CRBN and Ras pathway genes

Abstract: • The incidence of mutations within the MAPK pathway, the CRBN pathway, and TP53 is significantly increased in drug-refractory MM.• Mutations in CRBN might contribute to IMiD resistance in drug-refractory MM.In this study, targeted sequencing to screen 50 multidrug refractory multiple myeloma (rMM) patients was performed by using the Multiple Myeloma Mutation Panel. Patients were pretreated with both immunomodulatory drugs (IMiDs) and proteasome inhibitors (PIs), and 88%, 78%, and 68% were refractory to an IMi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 207 publications
(224 citation statements)
references
References 59 publications
7
191
0
1
Order By: Relevance
“…We did however analyze the 895 patients sequenced as part of the MMRF CoMMpass trial and found only one mutation in PSMC6 , however a significant number of patients with other 19S subunits mutations (3.7%) are noted. Most of these patients are newly diagnosed and we hypothesize that mutations would be enriched in resistant/refractory cases to PIs, in line with our recent findings in patients that have relapsed after treatment with IMiDs (19). Thus, CRBN, the gene targeted by IMiDs, was found mutated in only 0.2% of newly diagnosed MM (https://research.themmrf.org/rp/mycommpass), but in 12% of patients refractory to IMiDs therapies with mutations in the CRBN pathway in at least 22% of the same patients and probably higher since structural variations were not analyzed (19).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We did however analyze the 895 patients sequenced as part of the MMRF CoMMpass trial and found only one mutation in PSMC6 , however a significant number of patients with other 19S subunits mutations (3.7%) are noted. Most of these patients are newly diagnosed and we hypothesize that mutations would be enriched in resistant/refractory cases to PIs, in line with our recent findings in patients that have relapsed after treatment with IMiDs (19). Thus, CRBN, the gene targeted by IMiDs, was found mutated in only 0.2% of newly diagnosed MM (https://research.themmrf.org/rp/mycommpass), but in 12% of patients refractory to IMiDs therapies with mutations in the CRBN pathway in at least 22% of the same patients and probably higher since structural variations were not analyzed (19).…”
Section: Discussionsupporting
confidence: 87%
“…PSBM5 mutations have been identified frequently in MM cell line but are not found in newly diagnosed patients (17, 18) while XBP-1 mutations have also been seen but are also found in less than 1% of newly diagnosed MM cases. Indeed the mutation prevalence of these genes combined is only 2% in supposedly PI refractory patients (19). XBP1 knock down experiments have shown correlation with BTZ resistance (14, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Cereblon (encoded by CRBN ) is important in mediating the anti-myeloma activity of the IMiD class of therapeutics, and therefore the pattern of mutations seen in CRBN is truncation or deleterious missense mutation in critical functional domains 12. The missense mutation we detected (Pro382Arg) has not been previously described in myeloma but is in the IMiD-binding domain next to a previously described missense mutation 13. No mutations in other genes associated with IMiD resistance ( IKZF1 , IKZF3 or IRF4 ) were identified.…”
Section: Resultsmentioning
confidence: 57%
“…• Some preliminary attempts aimed at introducing NGS-based technologies during routine diagnostic workup for MM have been made [68,69,70,71], and certainly will continue to be implemented.…”
Section: Key Issuesmentioning
confidence: 99%